2019
DOI: 10.1111/mmi.14216
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the essentiality and function of the anti‐σM factors in Bacillus subtilis

Abstract: Bacteria use alternative sigma factors to adapt to different growth and stress conditions. The Bacillus subtilis extracytoplasmic function sigma factor SigM regulates genes for cell wall synthesis and is crucial for maintaining cell wall homeostasis under stress conditions. The activity of SigM is regulated by its anti-sigma factor, YhdL, and the accessory protein YhdK. Here, we show that dysregulation of SigM caused by the absence of either component of the anti-sigma factor complex leads to toxic levels of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 69 publications
3
18
0
Order By: Relevance
“…The concentrations and affinities of individual sigma factors influence their competition for the core RNAP [59,60]. While sigma factor competition is best studied in E. coli, it has been observed in other organisms, including P. aeruginosa [47,59,[61][62][63]. One such example in P.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations and affinities of individual sigma factors influence their competition for the core RNAP [59,60]. While sigma factor competition is best studied in E. coli, it has been observed in other organisms, including P. aeruginosa [47,59,[61][62][63]. One such example in P.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of BcrC is primarily controlled by the extracytoplasmic function sigma factor M (14,30). While the physiological input triggering activation of M still remains elusive (31,32), the broad range of inducing conditions, including cell wall antibiotics, salt, ethanol, and others, suggests that it is not a specific chemical compound but rather a cellular cue upon cell envelope damage that activates the M response (33). Interestingly, despite the seemingly unrelated input stimuli for the BceAB and the BcrC resistance modules-with BceAB being activated by a "drugsensing" mechanism (antibiotic flux) and BcrC by a "damage-sensing" mechanismprevious work revealed that there is a high level of interdependency between the modules (26).…”
mentioning
confidence: 99%
“…However, full YhdL activity requires a second transmembrane protein, YhdK. Although a lack of σ M is well tolerated under unstressed conditions, the lack of the anti-σ M factors leads to a runaway activation of the autoregulated sigM operon, and overexpression of the σ M regulon [10]. A null mutation of yhdK leads to an ~100-fold elevation of σ M activity, morphological abnormalities, and slow growth [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although a lack of σ M is well tolerated under unstressed conditions, the lack of the anti-σ M factors leads to a runaway activation of the autoregulated sigM operon, and overexpression of the σ M regulon [10]. A null mutation of yhdK leads to an ~100-fold elevation of σ M activity, morphological abnormalities, and slow growth [10]. A null mutation in yhdL is lethal, but suppressors arise readily that have inactivated sigM and grow normally in unstressed conditions [4, 10].…”
Section: Introductionmentioning
confidence: 99%